Inflation and its Effects on the Indian Economy - Maheshwari, Neeta; Biyani, Rajeev (Indian Journal of Finance, 2012)
The Indian economy is affected by many factors. However, inflation is a major factor which affects the economy. The aim of this paper is to analyze the impact of inflation on the Indian economy. The major initiatives taken up by the Government of India and Reserve Bank of India to contain the inflation is discussed. The paper presents rate of inflation based on CPI. Furthermore, effect of RBI’s measures on rate of inflation is investigated. India’s growth rate for the last one decade is presented in this paper . The relationship between inflation and economy is a contagious issue, still, this paper attempted to investigate the effect of inflation on economic growth. It was found that there is no direct exclusive relationship between growth rate and inflation. However, high rate of inflation is harmful to the growth of the economy, but its mild dose may be able to sustain high growth. There is a trade-off between inflation and growth.